2010
DOI: 10.1007/s12570-010-0003-0
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of head size versus metaphyseal fit with the Austin Moore hemiarthroplasty

Abstract: Purpose It has previously been suggested that failure to achieve 70% metaphyseal fit with the Austin Moore prosthesis predisposes to subsidence and failure of the prosthesis secondary to stem loosening. We performed a radiological review to test this hypothesis, and determine whether a correlation existed between head size and metaphyseal fit of the uncemented Austin Moore hip prosthesis. Methods Post-operative radiographs of 102 uncemented Austin Moore hemiarthroplasty patients were retrospectively reviewed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In 2010, Nader N.T. Rehmatullah et al [25] showed an inverse correlation between prosthesis head size and metaphyseal fit in their study. They stated that AMP with head sizes greater than 49mm are likely to be loose, and in such cases, the use of an uncemented bipolar or cemented Hemiarthroplasty is recommended.…”
Section: Discussionmentioning
confidence: 79%
“…In 2010, Nader N.T. Rehmatullah et al [25] showed an inverse correlation between prosthesis head size and metaphyseal fit in their study. They stated that AMP with head sizes greater than 49mm are likely to be loose, and in such cases, the use of an uncemented bipolar or cemented Hemiarthroplasty is recommended.…”
Section: Discussionmentioning
confidence: 79%
“…At least 70% canal fill by the stem of the prosthesis at the level of lesser trochanter is necessary to avoid excessive subsidence of the prosthesis and pain according to Yau et al [10]. Rehmatullah et al [46] found an inverse relationship between prosthesis head size and metaphyseal fit. Austin Moore prosthesis with head size 42 mm had an average 84.5% fit whereas a 54 mm head had only 56% fit in their study.…”
Section: Discussionmentioning
confidence: 99%